Development of automated power efficient and load modeling system utilizing IEC 61850 file transfer service - Shokri M.S.M.; Rahim A.A.; Abidin I.Z. (Alpha Publishers, 2023)
Conventional load modeling methodologies consist of two existing approaches, which are the component based approach and the measurement based approach. The measurement based approach offers several advantages and can overcome certain limitations resulted from component based approach implementation. By using the measurement based approach, the load model parameters can be estimated using power system disturbance records. Automated disturbance record collection can be performed by utilizing IEC 61850, i.e. the international communication standard for substation and power utility automation. This paper presents the design and development of automated load modeling system utilizing IEC 61850 file transfer service. The system architecture was designed based on the centralized disturbance record concentrator for distributed recording devices. The system was developed to perform event triggered disturbance record acquisition, where IEC 61850 file transfer service was utilized for automatic disturbance record retrieval. The proposed system was tested to automatically retrieve disturbance records from three multivendor IEC 61850 compliant relays. It was found that the root directory for each relay are not standardized eventhough the communication is standardized according to IEC 61850. The proposed system was then tested and verified by simulating actual disturbance measurements into the relays. The system was able to automatically retrieve the disturbance records and perform a fairly accurate curve fit to the actual disturbance measurements based on the automatically generated load model parameters. The results are encouraging for the actual implementation and deployment of actual substations. 2020 Alpha Publishers. All rights reserved.